Drug utilization study in ophthalmology department at a tertiary care hospital - Ahluwalia, Pritpal Singh; Baig, Mirza Shiraz; Awargaonkar, Amarnath; Nandedkar, Varsha (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Drug utilisation studies in present clinical practice have played significant role to promote rational drug use in the current health care system. The aim of present study was to analyse the prescribing pattern of drugs for various ocular conditions in Ophthalmology Department of Government Medical College and Hospital, Aurangabad, Maharashtra, India. Methods: Study was prospective, observational open label and descriptive clinical study which included 100 patients in OPD and IPD during November 2018 to February 2019 fulfilling inclusion criteria. Results: Out of the 100 study subjects, 56% were males and 46% were females, with the maximum number of patients falling in the age group 61-80 years. 38.26% patients received antibiotics as most prescribed drug while 69 % patients received analgesics and 47% anti-inflammatory. Among the antibiotics prescribed, fluoroquinolones were the most prescribed antimicrobial class. WHO prescribing indicators as analysed from the data collected were: average number of drugs per prescriptions was 3.79. Percentage of medicines prescribed by branded name- 33.79% and generic were 66.21%. 54% of the total drugs prescribed were from the National List of Essential Medicines 2017. Conclusions: Ocular ailments and conditions are frequently associated with high levels of utilization of drugs for their treatment. Thus, analysis of utilization of these drugs becomes very essential. In the present study, the drugs prescribed at our tertiary care hospital were found rational.